2019
DOI: 10.1016/j.envint.2018.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term traffic-related air pollution on the metabolome – Results from two metabolome-wide experimental studies

Abstract: Exposure to traffic-related air pollution (TRAP) has been associated with adverse health outcomes but underlying biological mechanisms remain poorly understood. Two randomized crossover trials were used here, the Oxford Street II (London) and the TAPAS II (Barcelona) studies, where volunteers were allocated to high or low air pollution exposures. The two locations represent different exposure scenarios, with Oxford Street characterized by diesel vehicles and Barcelona by normal mixed urban traffic. Levels of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 22 publications
0
37
1
2
Order By: Relevance
“…High-resolution metabolomics (HRM), a high-throughput method involving the identification and quantitation of thousands of metabolic features associated with exogenous exposure and endogenous processes, has emerged as a powerful tool to improve exposure estimation to complex environmental mixtures (Bundy et al 2009; Miller and Jones 2014). Several studies have previously demonstrated that metabolomics sensitively reflect internal metabolic perturbations following exposures to urban air pollution (Huang et al 2018; Jeong et al 2018; Ladva et al 2018; Liang et al 2018b; van Veldhoven et al 2019; Vlaanderen et al 2017). These initial findings are promising and have led us to hypothesize that TRAP-specific metabolic markers of exposure and response may be detectable, especially in individuals thought to most susceptible to risk from this pollutant source (i.e., asthma).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution metabolomics (HRM), a high-throughput method involving the identification and quantitation of thousands of metabolic features associated with exogenous exposure and endogenous processes, has emerged as a powerful tool to improve exposure estimation to complex environmental mixtures (Bundy et al 2009; Miller and Jones 2014). Several studies have previously demonstrated that metabolomics sensitively reflect internal metabolic perturbations following exposures to urban air pollution (Huang et al 2018; Jeong et al 2018; Ladva et al 2018; Liang et al 2018b; van Veldhoven et al 2019; Vlaanderen et al 2017). These initial findings are promising and have led us to hypothesize that TRAP-specific metabolic markers of exposure and response may be detectable, especially in individuals thought to most susceptible to risk from this pollutant source (i.e., asthma).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen of the retained studies had a cross-sectional design (21%) [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], and twelve were experimental (15%) (i.e., three randomized trials on metabolomic profile alterations [90,91] or clinical health outcomes [92] following administration of the experimental exposure; two open label cross-over trials exploring metabolomic and clinical effects of an experimental (juice) [93,94] or environmental (airborne and grass pollen) intervention [95], and seven experimental non-randomized studies). Five studies were case-control (6%) [94,[96][97][98][99] and three case-control studies nested in cohorts (4%) [100][101][102].…”
Section: Description Of the Selected Articlesmentioning
confidence: 99%
“…The endogenous response following administration of a specific exposure was assessed using metabolomics in 9 experimental studies (12%) and in one cross-sectional study [88]. The experimental interventions were mainly exposure to air contaminants (n = 4), of which one was of occupational nature [91,[125][126][127]. Other studies examined the effects of juice intake (n = 2) [94,128], disinfection by-products (n = 2) [93,125], and controlled food intake (n = 1) [60].…”
Section: Interventionsmentioning
confidence: 99%
“…É interessante notar que todos esses mecanismos estão associados ao balanço energético (BAYEVA; SAWICKI; ARDEHALI, 2013; COX; CLARKE, 2014). Estudos prévios demonstraram por meio de análise de metabolômica que a exposição ao AmbPol pode afetar o metabolismo de lipídios e aumentar a produção de corpos cetônicos em ratos (MILLER et al, 2015) e humanos (MILLER et al, 2016;VAN VELDHOVEN et al, 2019).…”
Section: Perfil Inflamatóriounclassified
“…Com relação as possiblidades metodológicas na abordagem para o problema, estudos prévios utilizaram uma técnica para análise ampla de metabólitos, a metabolômica. Foi demonstrado que ela é uma ferramenta eficaz na avaliação do metabolismo após EFA (NIEMAN et al, 2012(NIEMAN et al, , 2013(NIEMAN et al, , 2014 e também das alterações metabólicas após exposição aos poluentes (VAN VELDHOVEN et al, 2019). Em um interessante estudo, foi demonstrado inclusive, que após exercício de baixa intensidade em uma câmara de exposição ao O3, as vias metabólicas relacionadas ao metabolismo de lipídios e produção de corpos cetônicos são impactadas em ratos (MILLER et al, 2015) e humanos (MILLER et al, 2016).…”
Section: Conclusãounclassified